Analisis Kinerja Sensor TF-Mini LiDAR untuk Pengukuran Jarak - Fardiansyah Nur Aziz; Masduki Zakarijah (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
The digitalization development is accelerating, making it possible to measure the distance without touching the objects. Light detection and ranging (LiDAR) sensors are widely available on the market as components for distance measurement. Numerous studies on LiDAR sensor application have been conducted, including research on automated guided vehicle (AGV) robots, quadcopters, and tropical vegetation mappings. Previous research focused on LiDAR sensor application but did not evaluate its precision and features in depth. There are possibilities that the components’ performances do not conform with the technical data standards. This study presents the performance testing results of a TF-Mini LiDAR sensor for distance measurement. This TF-Mini LiDAR sensor testing used an experimental method. The sensor performance was determined by the maximum distance reading, accuracy level, objects’ color effect, tilt, and material type of objects being read. The testing results showed the TF-Mini LiDAR sensor had an accuracy rate of 3.17% in the range of 0.3 m to 6 m and 3.27% in the range of 6 m to 12 m, with a maximum reading distance of 10 m. Blue and iron were the most readable hue and material, with an average error rate of 2.78% and 3.2%, respectively. The distance reading results on flat objects with a tilt between 10° and 80° (quadrant 1) exceeded the actual distance as objects’ angle tilt increased, with the yielded error average of 7%. The average inaccuracy for flat objects with a tilt between 100° and 170° (quadrant 2) was 2.75%. Additionally, the distance reading accuracy improved as the objects’ degree of tilt increased. Based on the testing results, the TF-Mini LiDAR sensor could measure distances more precisely when the detected item was between 0.5 m and 10 m away, has a non-light-absorbing color and material, and is in the straight state.